Leveraging Economies of Scale via Collaborative Interdisciplinary Global Health Tracks (CIGHTs): Lessons From Three Programs. (20th August 2019) - McHenry, Megan S.; Baenziger, Jennifer T. H.; Zbar, Lori G.; Mendoza, Joanne; den Hartog, Julia R.; Litzelman, Debra K.; Pitt, Michael B.
Abstract : As interest in global health education continues to increase, residency programs seeking to accommodate learners' expectations for global health learning opportunities often face challenges providing high-quality global health training. To address these challenges, some residency programs collaborate across medical specialties to create interdepartmental global health residency tracks or collaborative interdepartmental global health tracks (CIGHTs). In this Perspective, the authors highlight the unique aspects of interdepartmental tracks that may benefit residency programs by describing three established U.S.-based programs as models: those at Indiana University, Mount Sinai Hospital, and the University of Virginia. Through collaboration and economies of scale, CIGHTs are able to address some of the primary challenges inherent to traditional global health tracks: lack of institutional faculty support and resources, the need to develop a global health curriculum, a paucity of safe and mentored international rotations, and inconsistent resident interest. Additionally, most published global health learning objectives and competencies (e.g., ethics of global health work, pre-departure training) are not discipline-specific and can therefore be addressed across departments—which, in turn, adds to the feasibility of CIGHTs. Beyond simply sharing the administrative burden, however, the interdepartmental learning central to CIGHTs provides opportunities for trainees to gain new perspectives in approaching global health not typically afforded in traditional global health track models. Residency program leaders looking to implement or modify their global health education offerings, particularly those with limited institutional support, might consider developing a CIGHT as an approach that leverages economies of scale and provides new opportunities for collaboration.